Enhanced structural, optical, and photocatalytic activities of Cd–Co doped Zn ferrites for degrading methyl orange dye under irradiation by visible light. (February 2022) - Shakil, M.; Inayat, Usama; Khalid, N.R.; Tanveer, Muhammad; Gillani, S.S.A.; Tariq, N.H.; Shah, Attaullah; Mahmood, Arshad; Dahshan, A.
Abstract: In this study, Cd–Co doped Zn ferrites (Cdx Zn1-x Co0.25 Fe1.75 O4 ; x = 0.0, 0.25, 0.5, and 0.75) were successfully synthesized using a facile sol–gel method for the first time. Furthermore, the prepared samples were utilized as catalysts in the degradation of methyl orange (MO) dye for wastewater treatment applications. Cubic particles with the Fd3m space group and spinel structure were characterized by field emission scanning electron microscopy and X-ray diffraction, respectively. Fourier transform-infrared and Raman spectroscopy analysis confirmed the presence of various functional groups, active sites, and a spinel structure. The optical properties were investigated by photoluminescence spectroscopy, which determined the emission spectrum in the range from 403 to 411 nm. The photocatalytic activity was assessed based on the degradation of MO dye. The ultravioletvisible absorption spectra showed that the sample with x = 0.75 (Cd0.75 Zn0.25 Co0.25 Fe1.75 O4 ) obtained the highest degradation efficiency of 82% after 120 min under irradiation by visible light due to the active octahedral lattice sites and prevention of electron/hole pair recombination. Highlights: Zinc ferrites synthesized sol–gel method. Raman modes and vibrational modes confirmed spinel structure of all samples. Photoluminescence intensity decreased Cd doping amount increased. Photocatalytic activity assessed based on degradation of methyl orange dye. Maximum degradation efficiency with x = 0.75 (Cd0.75 Zn0.25 Co0.25 Fe1.75 O4 .